When the Border is a River: A Journey Along the Salween River-Border (Open Rivers, 2024)

(untitled)
Rivers might appear to be a natural or even an expedient way to demarcate political borders. Yet rivers are always in flux as flows of water, sediments, and fish and aquatics shift with the rains and tides. For rivers to serve as borders, individuals, communities, and governments engage in a range of efforts, such as erecting walls, fences, or signs, underlining the reality that borders are actively constructed through contested sociopolitical processes and in everyday life.